Putative Immunological Functions of Inducible Skin-Associated Lymphoid Tissue in the Context of Mucosa-Associated Lymphoid Tissue - Kogame, Toshiaki; Kabashima, Kenji; Egawa, Gyohei (Frontiers in Immunology, 2021)
Acquired immunity is orchestrated in various lymphoid organs, including bone marrow, thymus, spleen, and lymph nodes in humans. However, mucosa-associated lymphoid tissue (MALT) is evolutionally known to be emerged in the oldest vertebrates as an immunological tissue for acquired immunity, much earlier than the advent of lymph nodes which appeared in endotherms. Furthermore, the lymphocytes which developed in MALT are known to circulate within the limited anatomical areas. Thus, MALT is comprehended as not the structure but the immune network dedicated to local immunity. As for the skin, skin-associated lymphoid tissue (SALT) was previously postulated; however, its existence has not been proven. Our group recently showed that aggregations of dendritic cells, M2 macrophages, and high endothelial venules (HEVs) are essential components to activate effector T cells in the murine contact hypersensitivity model and termed it as inducible SALT (iSALT) since it was a transient entity that serves for acquired immunity of the skin. Furthermore, in various human skin diseases, we reported that the ectopic formation of lymphoid follicles that immunohistochemically analogous to MALT and regarded them as human counterparts of iSALT. These data raised the possibility that SALT can exist as an inducible form, namely iSALT, which shares the biological significance of MALT. In this article, we revisit the evolution of immunological organs and the related components among vertebrates to discuss the conserved functions of MALT. Furthermore, we also discuss the putative characteristics and functions of iSALT in the context of the MALT concept.